Analysing driver behaviour within dilemma zone at signalised intersection: The observational and survey methods / Haryati Fauzi and Aznoora Osman - Fauzi, Haryati; Osman, Aznoora (UiTM Cawangan Perlis, 2017)
Signalised intersections is deemed amongst complex issues in road safety control system. Due to the growing number of crashes at signalised intersection every year in Malaysia, this research aims at understanding driver behaviour at signalised intersection. This paper discusses the methods to analyse driver behaviour at signalised intersection, which consist of field data collection using video recording technique and administration of a survey pertaining to driving behaviour within dilemma zones with selected participants (car driver).The methods are designed to gain a better understanding of driver behavioursthat influence their decisionmaking of non-compliance at signalised intersection, within the dilemma zones.The main goal is to reveal driver responses at dilemma zone during amber signal light, with respect to the vehicle distance from stop line, signal timing and approaching speed.